Implementasi Sistem Customer Relationship Management (CRM) Berbasis Web Menggunakan NodeJS, React, dan MySQL: Studi Kasus Pengembangan CRM-App - Nur Aisyah; Firhan Samudzky (Journal of Information Systems and Business Technology, 2025)
The CRM (Customer Relationship Management) system is a digital platform aimed at strengthening customer loyalty and engagement by systematically recording and monitoring interactions. This research involves the creation and deployment of a web-based CRM application, developed using ReactJS for the user interface, NodeJS for the server-side logic, and MySQL as the data storage solution. Agile methodology was adopted to support quick, iterative development and adaptability to changing requirements. Black-box testing was used to assess 10 key system features, with results showing that 90% of them worked as intended, while one feature experienced a failure during the package update process. This CRM solution proves to be a valuable tool for small to medium enterprises seeking to improve their customer management efficiency..